Beyond the Black lady : sexuality and the new African American middle class - Thompson, Lisa B., 1965- (New Black studies series., 2009)
The author explores the representation of black middle class female sexuality by African American women authors in narrative literature, drama, film, and popular culture, showing how these depictions reclaim black female agency and illustrate the difficulties black women confront in asserting sexual agency in the public sphere. Drawing on the work of black feminist theorists, the author examines symptomatic autobiographies, novels, plays, and key episodes in contemporary American popular culture, including works by Anita Hill, Judith Alexa Jackson, P. J. Gibson, Julie Dash, Kasi Lemmons, Jill Nelson, Lorene Cary, and Andrea Lee.